PENERAPAN ADAPTASI KEBIASAAN BARU DALAM MENCEGAH PENULARAN COVID-19 DI SEKOLAH DASAR KEC. MANONJAYA KAB. TASIKMALAYA - Sri Maywati; Santiana Santiana; Lesi Oktiwanti; Irani Hoeronis (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2021)
School institutions are one of the areas of community activity that must implement health protocols in order to prevent the spread of covid-19. The implementation of health protocols in the prevention of Covid-19 requires the support of various components in schools including the commitment of policy maker, community support and facilities as well as increasing the capacity to empowerment of school communities. The purpose of this activity is to provide support to schools in implementing the adaptation of new habits in schools. A total of 34 teachers / staff from 4 schools were involved in this activity. The activity stages include advocacy, creative supportive environment and social support  as well as community empowerment. The results of this activity obtained the same perception and strong commitment from the principal regarding Covid must be a concern. Build an atmosphere and create a supportive environment by building community support (inside / outside of school) as well as providing physical facilities in implementing AKB. Community empowerment activities are carried out through ToT (Training of Trainers) regarding healthy behavior in adapting to new habits in schools in increasing knowledge and building positive attitudes about Covid-19. Suggestions are given to schools to keep commitments and provide support in providing facilities at schools and teachers / staff are expected to convey information about the adaptation of new habits to all students. Keywords : Adaptation to new habits, covid-19, school